Urban-rural disparities and determinants of stunting among children under five in Indonesia - Merita Yumna Nisrina; Evi Susanti Sinaga (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Stunting remains a significant public health issue in Indonesia, particularly among children under five. Various risk factors across rural and urban settings influence it. Understanding these factors is critical to designing effective interventions that support optimal child growth and development. Purpose: To analyze the urban-rural gap and determinants of stunting in toddlers in Indonesia Method: A cross-sectional study used secondary data from the 2021 Indonesian Nutritional Status Survey. A total of 11,715 children aged 0–59 months were included through total sampling. Independent variables examined included food insecurity, breastfeeding, maternal class participation, family planning, sanitation, drinking water access, dietary diversity, mother’s education, and place of residence. Chi-square tests were used for bivariate analysis, and statistical significance was determined at p < 0.05. Results: Stunting prevalence was 28.6%. Bivariate analysis revealed that food insecurity, lack of breastfeeding, low maternal education, poor sanitation, absence of family planning, non-participation in mother’s classes, and rural residence were significantly associated with stunting (p < 0.05). Access to drinking water and dietary diversity were not significantly associated with stunting. Stunting was higher in rural areas (74.4%) than in urban areas (25.6%). Conclusion: Socioeconomic, behavioral, and environmental factors influence stunting in children under five. Effective stunting prevention strategies should improve maternal education, access to health services, nutrition awareness, sanitation infrastructure, and rural health equity. A multisectoral, community-based approach is essential to reducing stunting and supporting healthy child development in Indonesia.